The Influence of QRIS and Cash Payment Usage on Halal Food MSME Purchasing Decisions among Muslim Generation Z in Surabaya - Nadzifa Ahya Nurdiana; Fira Nurafini (International Conference on Islamic Economic (ICIE), 2026)
The rapid growth of the halal food industry and the increasing adoption of digital payment systems have transformed consumer purchasing behavior, particularly among Generation Z. This study aims to examine the effects of QRIS usage and cash payment on purchasing decisions for halal food MSMEs among Muslim Generation Z in Surabaya. A quantitative approach with a causal associative research design was employed. Data were collected through questionnaires from 169 respondents selected using purposive sampling and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS. The results indicate that QRIS usage has a positive and significant effect on purchasing decisions (β = 0.720; t = 9.510; p < .001). Meanwhile, cash payment also has a positive and significant effect (β = 0.139; t = 2.084; p = .037), although its influence is considerably weaker than that of QRIS. These findings suggest that QRIS is the dominant payment method influencing purchasing decisions among Muslim Generation Z consumers in halal food MSMEs, while cash payment remains a relevant alternative transaction method. This study provides empirical evidence comparing the influence of digital and conventional payment methods on purchasing decisions and offers practical implications for halal food MSMEs in developing payment strategies that better align with consumer preferences.